Distribuição das espécies de peixes de interesse ornamental ao longo da região hidrográfica do Xingu - Estado do Pará - SOARES, Ellen Regina Lima (2019)
Fishing in the Amazon region stands out for its richness and operated by the dependence of the population to this activity. In the international aquarium Amazonian species have great potential and attractive international demand is growing, with more than 20 million fish exported from the region. Among the seven river basin districts of the state of Pará in the Xingu region stands to make great ictiodiversidade, and the fishery started in the municipality of Altamira - PA, with the capture of fish of the family Loricariidae, and is still one of the most relevant business activities. Through literature on the geographic distribution of species of ornamental fish occur in the basin of the Xingu, the information was entered into spreadsheets, which served as the basis for a table with the composition of species already collected in the region, separated order, family, genus and species or morphospecies. Location data standardized UTM (Universal Transverse Mercator) were then plotted to produce maps of the species divided according to the order to which he belonged. Were obtained 240 species divided into 9 orders, and the most representative Characiformes and Siluriformes with 77% market share. The families with the highest representation were: Loricariidae, Characidae and Cichlidae with 33%, 21% and 13% respectively. Among the total species, 31 were considered endemic to the basin of the Xingu. With the spatial distribution of the data showed that much of the work in the region of the Xingu basin, focused on the area known as 'Grand Tour', in view of environmental impact studies conducted during the planning of the construction of the Hydroelectric Plant Belo Monte. It follows that the pressure exerted by the selective fishing of ornamental species, as well as the environmental changes generated by the construction of Belo Monte dam, can cause mortality and reduced much of diversity of fish of the Xingu river basin, so this study could serve as a basis for future conservation measures.